The Development of Android Application Familiarization to Variety of Profession Based on Applied Science Cluster - Noor, Khilda Wulidatin; Hidayat, Dede Rahmat; Hanim, Wirda (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study is to develop a familiarization to the variety of professions that can be familiarized by classifying professions based on applied science clusters in Indonesia in accordance with the Constitution of the Republic of Indonesia Number 12 of 2012 concerning Higher Education in article 10 section 2 which reads: "... (a) religion knowledge; (b) humanities; (c) social science clusters; (d) natural sciences; (e) formal science clusters; and (f) applied science, with android applications. Variety of professions is an activity carried out by someone to support themselves and their families where the profession is governed by professional ethics where the ethics of the profession applies only to those professions. Besides the familiarization of various professions since elementary school age is a strategic choice in preparing future generations, the variety of professions is needed by students from the age of elementary school, as a reference for their ideals. Following the times, the familiarization of various professions can be applied in technology. The method used is research and development, which develops Android applications, based on the applied science clusters. It is expected that students can get to know and choose a picture related to their future career.